Ethnomedicinal Uses of Plant Resources in Puranchaur Village, Kaski, Nepal - Gautam, Subash; Timilsina, Sachin (Ethnobotany Research and Applications, 2022)
Background: Plants are being utilized worldwide as a primary health care need. The reliance is also prevalent in Nepal, aided by its high biological diversity. The rich floral composition in Puranchaur offers a remarkable opportunity for ethnomedicinal research. This study aimed to index the ethnomedicinal knowledge of plant species of Puranchaur of Kaski district. Methods: Open-ended semi-structured questionnaires were conducted to collect data during October 2021 to November 2021 using Key Informant Interview (KII) and Focus Group Discussions (FGDs). The reported traditional uses were asked with traditional healers and cross-validated with previously published literature. Data were analyzed and represented in a tables, graphs, radar, and pie charts. Results: A total of 131 medicinal plants, belonging to 67 families and 119 genera were recorded to treat 156 different ailments. Poaceae and Asteraceae families represent the maximum number of plants used (N=11). Herbs were most frequently used (N=67) among the different habits of plants. The most preferred form of medication was paste (N=56), followed by juice (N=54), raw (N=47), powder (N=34), decoction (N=19), and cooked (N=10). Leaf cured a large number of diseases (N=112). Commonly used plant parts were seed (N=67) followed by leaf (N=58), flower (N=32), root (N=31), stem (N=29), fruit (N=25), bark (N=22), whole plant (N=13), latex (N=7), tuber (N=6), rhizome (N=5), bulb (N=1), and cornsilk (N=1). Conclusion: This study concluded that documentation and preservation of biodiversity and its associated knowledge is necessary which could generate further research activities. Ocimum sanctum is the most frequently cited medicinal plant with Relative Frequency Citation (RFC) 0.44 followed by Acorus calamus L. (0.41), Zingiber officinale Roscoe (0.40), Centella asiatica (L.) Urb. (0.38), and Mentha spicata L. (0.37) and the Informant Consensus Factor (Fic) was found to be highest for digestive alignment category (0.8) and lowest for ear (0.00). The pharmacological and phytochemical studies of these medicinal plants should be carried out for their scientific validation. Keywords: Diseases and ailments, Ethnomedicine, Indigenous knowledge, Medicinal plants, Puranchaur